Cognition and brain oxygen metabolism improves after bariatric surgery-induced weight loss: A pilot study - Anwar, Nareen; Tucker, Wesley J.; Puzziferri, Nancy; Samuel, T. Jake; Zaha, Vlad G.; Lingvay, Ildiko; Almandoz, Jaime; Wang, Jing; Gonzales, Edward A.; Brothers, Robert Matthew; Nelson, Michael D.; Thomas, Binu P. (Frontiers in Endocrinology, 2022)
Objective: The primary objectives of this pilot study were to assess cognition and cerebral metabolic rate of oxygen (CMRO2) consumption in people with severe obesity before (baseline), and again, 2- and 14-weeks after sleeve gastrectomy bariatric surgery. Methods: Six people with severe/class 3 obesity (52±10 years, 5 females, body mass index (BMI) = 41.9±3.9 kg/m2), and 10 normal weight sex- and age-matched healthy controls (AM-HC) (48±6 years, 8 females, 22.8±1.9 kg/m2). Global CMRO2 was measured non-invasively using MRI and cognition using the Integneuro testing battery. Results: Following a bariatric-surgery induced weight loss of 6.4±2.5 kg (% total-body-weight-lost = 5.4) over two-weeks, cognition total scores improved by 0.8±0.5 T-scores (p=0.03, 15.8% improvement form baseline). Weight loss over 14-weeks post-surgery was 15.4±3.6 kg (% total-body-weight-lost = 13.0%) and cognition improved by 1.1±0.4 (p=0.003, 20.6% improvement from baseline). At 14-weeks, cognition was 6.4±0.7, comparable to 6.0±0.6 observed in the AM-HC group. Baseline CMRO2 was significantly higher compared to the AM-HC (230.4±32.9 vs. 177.9±33.9 µmol O2/min/100 g, p=0.02). Compared to baseline, CMRO2 was 234.3±16.2 µmol O2/min/100 g at 2-weeks after surgery (p=0.8, 1.7% higher) and 217.3±50.4 at 14-weeks (p=0.5, 5.7% lower) after surgery. 14-weeks following surgery, CMRO2 was similar to AM-HC (p=0.17). Conclusion: Bariatric surgery induced weight loss was associated with an increase in cognition and a decrease in CMRO2 observed 14-weeks after surgery. The association between weight loss, improved cognition and CMRO2 decrease should be evaluated in larger future studies.